1997
DOI: 10.1161/01.hyp.30.5.1289
|View full text |Cite
|
Sign up to set email alerts
|

Association of Calcitriol and Blood Pressure in Normotensive Men

Abstract: The purpose of this study was to clarify the possible associations between the serum 1,25-dihydroxyvitamin D (calcitriol) level and blood pressure. Cross-sectional analysis of data was performed. Data collected included levels of serum calcitriol, parathyroid hormone, serum calcium, and blood lead; blood pressure; dietary history; and demographic and anthropometric variables. One hundred normotensive male industrial employees made up the study population. Systolic blood pressure and diastolic blood pressure we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(110 citation statements)
references
References 32 publications
3
99
0
3
Order By: Relevance
“…Some studies have reported significantly higher vitamin D levels in hypertensive patients than normotensive patients (11,22), and this increase has been shown to be related to the activation of 1.25-hydroxylase via PTH (11). However, in accordance with our findings of significantly lower levels of vitamin D in hypertensive patients, vitamin D level has been reported to be lower in subjects with higher systolic and diastolic BP (24). Though these contradictory results may be related to the heterogeneous characteristics of the patient populations in the studies, it seems notable that no significant correlations were determined between mean 24-hour ASBP and ADBP and levels of PTH, vitamin D, and calcitonin in our patients with essential hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have reported significantly higher vitamin D levels in hypertensive patients than normotensive patients (11,22), and this increase has been shown to be related to the activation of 1.25-hydroxylase via PTH (11). However, in accordance with our findings of significantly lower levels of vitamin D in hypertensive patients, vitamin D level has been reported to be lower in subjects with higher systolic and diastolic BP (24). Though these contradictory results may be related to the heterogeneous characteristics of the patient populations in the studies, it seems notable that no significant correlations were determined between mean 24-hour ASBP and ADBP and levels of PTH, vitamin D, and calcitonin in our patients with essential hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, there is evidence that 125VTD suppresses the renin gene expression (65) and regulates the growth and proliferation of vascular smooth cells and cardiomyocytes (66). Clinical studies have associated low levels of vitamin D with blood pressure (67,68), coronary artery calcification (69), and cardiovascular diseases, such as myocardial infarction (70), acute stroke (71), congestive heart failure (72). Recently, in the Framingham Offspring Study, vitamin D deficiency has also been associated with incident cardiovascular diseases (64).…”
Section: Vitamin D and Cardiovascular Diseasesmentioning
confidence: 99%
“…Epidemiological and clinical studies have also reported an inverse association between vitamin D status and blood pressure (Kristal-Boneh et al, 1997;Scragg et al, 2007); serum 25-hydroxyvitamin D (25(OH)D) concentrations have been shown to inversely, albeit weakly, associated with hypertension or blood pressure in some (Kokot et al, 1981;Scragg et al, 2007), but not all studies (Snijder et al, 2007). The link between vitamin D and blood pressure may relate, in part, to the fact that vitamin D is a negative regulator of renin release, which is important in the regulation of blood pressure (Li et al, 2004).…”
Section: Introductionmentioning
confidence: 99%